Overexpression of a human potassium channel suppresses cardiac hyperexcitability in rabbit ventricular myocytes - Hanne Nuss; Eduardo Marbán; David C. Johns (1999)
The high incidence of sudden death in heart failure may reflect abnormalities of repolarization and heightened susceptibility to arrhythmogenic early afterdepolarizations (EADs). We hypothesized that overexpression of the human K+ channel HERG (human ether-a-go-go-related gene) could enhance repolarization and suppress EADs. Adult rabbit ventricular myocytes were maintained in primary culture, which suffices to prolong action potentials and predisposes to EADs. To achieve efficient gene transfer, we created AdHERG, a recombinant adenovirus containing the HERG gene driven by a Rous sarcoma virus (RSV) promoter. The virally expressed HERG current exhibited pharmacologic and kinetic properties like those of native IKr. Transient outward currents in AdHERG-infected myocytes were similar in magnitude to those in control cells, while stimulated action potentials (0.2 Hz, 37°C) were abbreviated compared with controls. The occurrence of EADs during a train of action potentials was reduced by more than fourfold, and the relative refractory period was increased in AdHERG-infected myocytes compared with control cells. Gene transfer of delayed rectifier potassium channels represents a novel and effective strategy to suppress arrhythmias caused by unstable repolarization.